Appraisal theory in translation studies—a systematic literature review - Qi, Yuan Liu; Lay, Hoon Ang; Waheed, Moniza; Mohd Kasim, Zalina (Universiti Putra Malaysia Press, 2022)
Appraisal theory (AT) is developed from Systemic Functional Linguistics. It focuses on the interpersonal meaning of the text, which expresses the speaker’s attitude and constructs ideological space. However, AT has developed quite lately in translation studies with certain achievements as well as limitations in the previous studies. Thus, this study conducted a literature review to generalize the status quo of studies applying AT in translation from 2011 to 2021. The method of this study is a systematic literature review that selected 27 articles from three databases based on the screening procedure of PRISMA 2020. It also used qualitative synthesis to analyze the contents of the included studies in terms of genres, research foci, application of AT as well as methodologies. This study finds that AT is widely used in analyzing translation shifts, especially in the text types of politics, news and literature with the foci of appraisal shifts, ideology and positioning. However, the number of translation studies applying AT is still limited, and there is potential to examine AT in other text types. Besides, there is also a lack of mixed method or corpus-based analysis. Therefore, this study provides a detailed review of AT in translation studies and reveals some research gaps that could enlighten future studies.